Shared autonomic phenotype of long COVID and myalgic encephalomyelitis/chronic fatigue syndrome - Peter Novak; David M. Systrom; Alexandra Witte; Sadie P. Marciano; Donna Felsenstein; Jeff M. Milunsky; Aubrey Milunsky; Joel Krier; Mark C. Fishman (PLoS ONE, 2026)
Introduction Long COVID and myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) are relatively common and disabling multisystem disorders that share overlapping features, including post-infectious onset and similar clinical manifestations such as brain fog, fatigue, muscle pain, and dysautonomia with orthostatic intolerance. These similarities suggest that Long COVID and ME/CFS may share common pathophysiological mechanisms, though the underlying mechanisms remain poorly understood, partly due to the difficulty in quantifying many of the symptoms. Materials and methods This retrospective study evaluated Long COVID and pre-COVID ME/CFS patients who completed autonomic testing between 2018 and 2023 at the Brigham and Women’s Faulkner Hospital Autonomic Laboratory. The evaluations included autonomic tests (Valsalva maneuver, deep breathing, tilt-table test, and sudomotor function) with capnography and transcranial Doppler monitoring of cerebral blood flow velocity (CBFv) in the middle cerebral artery, neuropathic assessment through skin biopsies for small fiber neuropathy (SFN), invasive cardiopulmonary exercise testing (ICPET), and laboratory analyses covering metabolic, inflammatory, autoimmune, and hormonal profiles. Results A total of 143 Long COVID and 170 ME/CFS patients were analyzed and compared to 73 healthy controls and 290 patients with hypermobile Ehlers-Danlos syndrome (hEDS). Tests revealed extensive similarities between Long COVID and ME/CFS, including reduced orthostatic CBFv (92%/88% in Long COVID/ME/CFS), mild-to-moderate widespread autonomic failure (95%/89%), presence of SFN (67%/53%), postural tachycardia syndrome (POTS) (22%/19%), neurogenic orthostatic hypotension (15%/15%) and preload failure (96%/92%, assessed in 25/66 Long COVID/ME/CFS). Patients with hEDS exhibited more severe peripheral neurodegeneration compared to the other groups. Laboratory tests did not distinguish between the conditions. Conclusion Both Long COVID and ME/CFS demonstrate dysregulation in cerebrovascular blood flow, autonomic reflexes, and small fiber neuropathy, suggesting that these conditions may share a common underlying pathophysiology. However, differing distributions of findings in patients with hEDS raise the question of whether these conditions represent distinct but overlapping syndromes or reflect a shared underlying pathway. Further research is required to clarify the relationship between these conditions and the potential underlying pathophysiological mechanisms.